BONDS AS AN INSTRUMENT OF FINANCING THE INVESTMENT PROJECTS OF LOCAL GOVERNMENTS IN POLAND - Główka, Gabriel (Acta Scientiarum Polonorum. Oeconomia, 2010)
The aim of the paper is to analyse and evaluate the role of municipal bonds in financing the local government’s investments. The investigation shows that local governments entities perceived advantages of gaining investment capital in the way of issues of municipal bonds. During 1996–2009 the value of yearly issues was raising gradually with quite high dynamic. It is especially important in the context of chance of realisation of many municipal investments under different EU support schemes. In such cases the financial means are necessary for co-financing of municipal investments.